Chile : Technical Assistance Report-Regulation and Supervision of Money Market Funds. (IMF Staff Country Reports; Country Report, 2022)
In September 2020 the CMF requested TA from the IMF in respect of a review of its regulatory regime for money market mutual funds. Between October 2020 and February 2021, organizational and preparatory work was undertaken by the mission team. This assessment relies on the information submitted by the CMF and other parties interviewed. While the mission did not include a review of supervisory case files, the descriptions of the current approach provided by the regulator, the central bank and industry are mutually consistent as between each other.